Measles Virus Epitope Presentation by HLA: Novel Insights into Epitope Selection, Dominance, and Microvariation - Schellens, Ingrid M.; Meiring, Hugo D.; Hoof, Ilka; Spijkers, Sanne N.; Poelen, Martien C. M.; van Gaans-van den Brink, Jacqueline A. M.; Costa, Ana I.; Vennema, Harry; Keşmir, Can; van Baarle, Debbie; van Els, Cécile A. C. M. (Frontiers in Immunology, 2015)
Immunity to infections with Measles Virus (MV) can involve vigorous HLA class I restricted CD8+ cytotoxic T cell (CTL) responses. MV, albeit regarded monotypic, is known to undergo molecular evolution across its RNA genome. To address which regions of the MV proteome are eligible for recognition by CD8+ cytotoxic T cells (CTL) and how different HLA class I loci contribute to the epitope display, we interrogated the naturally processed and presented MV peptidome extracted from cell lines expressing in total a broad panel of 16 different common HLA-A, -B and -C molecules. The repertoire and abundance of MV peptides were bona fide identified by nanoHPLC-MS-MS. Eighty-nine MV peptides were discovered and assignment to an HLA-A, -B or –C allele, based on HLA-peptide affinity prediction, was in most cases successful. Length variation and presentation by multiple HLA class I molecules was common in the MV peptidome. More than twice as many unique MV epitopes were found to be restricted by HLA-B than by HLA-A, while MV peptides with supra-abundant expression rates (>5,000 copies per cell) were rather associated with HLA-A and HLA-C. In total, fifty-nine regions across the whole MV proteome were identified as targeted by HLA class I. Sequence coverage by epitopes was highest for internal proteins transcribed from the MV-P/V/C and -M genes and for haemagglutinin. At the genome level, the majority of the HLA class I selected MV epitopes represented codons having a higher non-synonymous mutation rate than silent mutation rate, as established by comparison of a set of fifty-eight unique full length MV genomes. Interestingly more molecular variation was seen for the epitopes expressed at rates ≥1,000 copies per cell. These data for the first time indicate that HLA class I broadly samples the MV proteome and that CTL pressure may contribute to the genomic evolution of MV.